Era uma vez um cinema: o caso do Cine-Theatro Independência e os mecanismos de preservação do patrimônio de Santa Maria (RS) - Silva, Amanda Costa da (2013)
The central objective of this essay was to reflect about the Cine-Theatro Independência s process of tipping, at Santa Maria (RS), discussing the conflicts related to heritage preservation and memorials choices. This place was inaugurated in 1922 in the central square of the city. Throughout more than 70 years, it staged performances, meetings and reunions gatherings, besides daily views of movies. Although Santa Maria have other great representation spaces for the cultural scene of the city, Cine Independência was the only movie theater in town that went through a process of tipping. This process, however, went so nebulous and seemingly confused. Currently, the space is mischaracterized and houses the Popular Shopping of Santa Maria. Therefore, this study aimed to identify, from the site's history and the process of tipping, elements that were crucial to the well reached the current situation, performing a reflection on the conflicts that underlie this process. For this, a literature has developed in relation the city's history, its cultu ral spaces and Cine Independência, contextualizing with other major cities of the state, as preservationists regarding public policies and memory and heritage concepts. In addition, it was searched documentation linked to this process of tipping, as well, along with the city archives, images and articles published in journals. Finally, if conducted an interview with former mayor of Santa Maria, seeking thus to better understand how this process took place and the constitution of the Popular Shopping of Santa Maria